1994
DOI: 10.1093/ajh/7.8.717
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Immunoreactive Endothelin Levels in Patients With Pheochromocytoma

Abstract: Plasma immunoreactive endothelin-1 (ET-1) concentrations were measured in 44 patients with pheochromocytoma, 31 patients with essential hypertension, and 20 healthy control subjects. Plasma ET-1 concentrations in patients with pheochromocytoma were 18.2 +/- 3.2 fmol/mL (mean +/- SEM), which was significantly higher than those of essential hypertension and healthy control subjects (7.3 +/- 0.4, 7.1 +/- 0.4 fmol/mL, respectively, P < .01). Plasma ET-1 concentrations in patients with essential hypertension and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Significantly higher levels of ET-1 were seen in those with phaeochromocytoma compared with the 2 other groups, and, among these, the presence of hypertension was associated with the highest plasma ET-1 concentrations. These findings supported a role for ET-1 in the development of clinical hypertension, 44 although many solid cancers generate ET-1. In agreement with preclinical data, which suggested that the ET system was primarily activated in the more severe rodent models of BP elevation (such as deoxycorticosterone acetate-salt, Dahl salt-sensitive, and stroke-prone spontaneously hypertensive rats), the increased prepro-ET-1 message is found in the endothelium of small arteries of patients with moderate-tosevere hypertension.…”
Section: Essential Hypertensionsupporting
confidence: 53%
“…Significantly higher levels of ET-1 were seen in those with phaeochromocytoma compared with the 2 other groups, and, among these, the presence of hypertension was associated with the highest plasma ET-1 concentrations. These findings supported a role for ET-1 in the development of clinical hypertension, 44 although many solid cancers generate ET-1. In agreement with preclinical data, which suggested that the ET system was primarily activated in the more severe rodent models of BP elevation (such as deoxycorticosterone acetate-salt, Dahl salt-sensitive, and stroke-prone spontaneously hypertensive rats), the increased prepro-ET-1 message is found in the endothelium of small arteries of patients with moderate-tosevere hypertension.…”
Section: Essential Hypertensionsupporting
confidence: 53%
“…This raises the suspicion about the role of ET in the pathogenesis of primary hyperaldosteronism (16). In pheochromocytoma, ET stimulates catecholamine release by the adrenal medulla and is secreted excessively together with the catecholamines (11). Available data show that it is hardly likely that the pituitary is the source of elevated ET-1 secretion in the ACTH-dependent Cushing's syndrome caused by corticotropinoma, since it was found that this peptide was expressed by both ACTH-secreting bronchial carcinoid and corticotropinomas (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to patients with primary hvperaldosteronism. endothelin-1 is elevated in pheochromocytoma [83], Moreover, a patient with endothelinsecreting hemangioendothelioma exhibited hypertension which normalized after the tumor had been resected [84], Since at least two thirds are released abluminally towards the vascular smooth muscle cells, endothelin-1 plasma levels do not reflect local levels of the peptide [85]. Nev ertheless.…”
Section: Genetic Hypertensionmentioning
confidence: 99%